Patient perceptions and willingness to stop smoking prior to foot and ankle surgery. Issue 6 (November 2018) - Baker, Adam; Dean, Erin Prewitt; Ishikawa, Susan N.; Murphy, G. Andrew; Grear, Benjamin J.; Richardson, David R.
Abstract : Background: Much attention has been focused on the effects of cigarette smoking on surgical outcomes and bone healing. There has been a recent push to educate patients on the negative effects of smoking on orthopaedic injuries and surgery and to provide support to patients during the smoking cessation process. The goal of this study was to determine whether patients are aware of the orthopaedic effects of smoking and to determine their level of interest in a supervised smoking cessation program. Methods: A five-question survey was given to patients who were admitted smokers, along with a short explanation of the deleterious effects of smoking on bones, soft tissue, and wound healing. In addition to questions on how long and how much patients smoked, the survey included questions assessing the patient's knowledge of the deleterious effects of smoking and their willingness to stop smoking. Results: Two hundred thirty-seven patients completed the survey. Of these patients, 104 (44%) indicated that they were unaware of the effects that smoking had on bone and wound healing. Eighty-two percent (195/237) indicated that with this knowledge they would be interested in a smoking cessation program, with 188 (96%) indicating they would stop smoking if their surgery were delayed until they did. Eighteen percent (42/237) were not interested in a smoking cessation program. Conclusions: This study indicates that a short discussion of smoking cessation after injury or before elective foot and ankle surgery and referral to a smoking cessation program could positively affect outcomes in smokers undergoing foot and ankle procedures.